How Investment Motivation and Digital Literacy Affect Investment Interest Among University Students - Ni Made Indah Mentari; Tiara Carina; I Dewa Made Arik Permana Putra (Journal of International Conference Proceedings, 2022)
Restrictions on social activities during the Covid-19 pandemic have made students have more free time at home. To fill their free time, students become more diligent in seeking information digitally, one of which is about investment and stocks. Digital literacy and investment motivation make students have an interest in investing. The awareness of students as the younger generation to invest arises because they see that most people struggle not to have investment funds when they lose their jobs during the pandemic. This research aims to determine the effect of investment motivation and digital literacy on investment interest among university students. The samples were 380 students of the Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, were obtained using the stratified random sampling method. Data were analyzed using Multiple Linear Regression Analysis. The result showed that investment motivation and digital literacy significantly affected investment interest (sig. 0.00; Adjusted R2 = 0.475). According to the result, investment interest will be increased if students have higher investment motivation and digital literacy.Â Keywords: Investment Motivation, Investment Interest, Digital Literacy